Women in South African politics : rural Shangaan women in focus - Maluleke, Gavaza (2010)
The focus of this thesis is to challenge the single story of women in developing countries by examining Shangaan rural women in politics. Hannah Arendt‘s notion of ‗acting and speaking‘ and what she defines as the polis helps guides this study as it exposes these rural women‘s capability to act whilst simultaneously, stressing the problems associated with categories in the polis. Postcolonial feminists, Chandra Mohanty and Uma Narayan, provide the categories linked with women in developing countries and the issues created when such categories are used as forms of analysis. Themes such as culture, tradition and history are also dealt with in order to fully explain and generate a better understanding of these Shangaan rural women and their situation. The research material collected was through in-depth interviews with 10 female and 5 male councillors who are part of the Giyani Municipality. The interviews were conducted in Xitsonga which is the main language of the Giyani area. The study found that there are still issues of gender inequality within Shangaan society but transformation is underway. These rural women are actively participating in the polis and they are dispelling the label of powerless victims. This is important in that it shows that no matter how active these women are, when categories are used as forms of analysis, seeing these women as actors and agents of change is not possible.